Changes in musculoskeletal disease activity and patient-reported outcomes in patients with psoriatic arthritis treated with ixekizumab: results from a real-world US cohort - Tillett, William; Birt, Julie; Cavanaugh, Cristi; Jung, Yoojin; Vadhariya, Aisha; Ross, Sarah; Paulus, Jessica; Lubrano, Ennio (Frontiers in Medicine, 2023)
Ixekizumab has demonstrated efficacy in pivotal trials in patients with psoriatic arthritis (PsA), both those naïve to prior biologic therapy and those with prior inadequate response or intolerance to biologics; however, minimal information is currently available on the effectiveness of ixekizumab in routine clinical practice. The objective of this study was to investigate the clinical effectiveness of ixekizumab for the treatment of PsA over 6- and 12-month follow-up periods in a real-world setting.